Analyzing the work stress of psychologists in the clinical field, through their resilience and well-being - Calero Escurra, Ofelia (2020)
The purpose of this research work was to establish whether there is an association between resilience and psychological well-being in psychologists working in the clinical field, for this, 93 clinical psychologists were selected for graduate students at a public university in the city of Lima. They were evaluated with the Sánchez Cánovas Psycho-logical Well-being Scale (EBP) and the Wagnild and Young Resilience Scale (ER). The general results show a statistically significant moderate positive correlation between resilience and psychological well-being, that is, as, in psychologists working in the clinical setting, with postgraduate training, the capacity to be able to successfully transform the adversities that arise in life, allowing them to adapt and project themselves successfully to their context also increases their perception of their personal satisfaction.